The risks associated with percutaneous native kidney biopsies: a prospective study. Issue 3 (19th May 2022) - Andrulli, Simeone; Rossini, Michele; Gigliotti, Giuseppe; La Manna, Gaetano; Feriozzi, Sandro; Aucella, Filippo; Granata, Antonio; Moggia, Elisabetta; Santoro, Domenico; Manenti, Lucio; Infante, Barbara; Ferrantelli, Angelo; et al.
ABSTRACT: Background: The known risks and benefits of native kidney biopsies are mainly based on the findings of retrospective studies. The aim of this multicentre prospective study was to evaluate the safety of percutaneous renal biopsies and quantify biopsy-related complication rates in Italy. Methods: The study examined the results of native kidney biopsies performed in 54 Italian nephrology centres between 2012 and 2020. The primary outcome was the rate of major complications 1 day after the procedure, or for longer if it was necessary to evaluate the evolution of a complication. Centre and patient risk predictors were analysed using multivariate logistic regression. Results: Analysis of 5304 biopsies of patients with a median age of 53.2 years revealed 400 major complication events in 273 patients (5.1%): the most frequent was a ≥2 g/dL decrease in haemoglobin levels (2.2%), followed by macrohaematuria (1.2%), blood transfusion (1.1%), gross haematoma (0.9%), artero-venous fistula (0.7%), invasive intervention (0.5%), pain (0.5%), symptomatic hypotension (0.3%), a rapid increase in serum creatinine levels (0.1%) and death (0.02%). The risk factors for major complications were higher plasma creatinine levels [odds ratio (OR) 1.12 for each mg/dL increase, 95% confidence interval (95% CI) 1.08–1.17], liver disease (OR 2.27, 95% CI 1.21–4.25) and a higher number of needle passes (OR for each pass 1.22, 95% CI 1.07–1.39), whereas higher proteinuria levels (OR for each g/day increase 0.95, 95% CI 0.92–0.99) were protective. Conclusions: This is the first multicentre prospective study showing that percutaneous native kidney biopsies are associated with a 5% risk of a major post-biopsy complication. Predictors of increased risk include higher plasma creatinine levels, liver disease and a higher number of needle passes. Graphical Abstract: